2010
DOI: 10.2514/1.41420
|View full text |Cite
|
Sign up to set email alerts
|

Geometric Filtration Using Proper Orthogonal Decomposition for Aerodynamic Design Optimization

Abstract: When carrying out design searches, traditional variable screening techniques can find it extremely difficult to distinguish between important and unimportant variables. This is particularly true when only a small number of simulations are combined with a parameterization that results in a large number of variables of seemingly equal importance. Here, the authors present a variable reduction technique that employs proper orthogonal decomposition to filter out undesirable or badly performing geometries from an o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
45
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(47 citation statements)
references
References 35 publications
(48 reference statements)
0
45
0
Order By: Relevance
“…New aerofoil shapes can then be constructed as a linear combination of these modes where the fidelity of the construction is determined by the number of modes used. This technique was first employed by Toal et al [34] then by Ghoman et al [35] and Poole et al [36]. Ghoman et al [35] used a series of supercritical aerofoils to derive the modes and showed that other supercritical aerofoils could efficiently be reconstructed.…”
Section: F Svd Methodsmentioning
confidence: 99%
“…New aerofoil shapes can then be constructed as a linear combination of these modes where the fidelity of the construction is determined by the number of modes used. This technique was first employed by Toal et al [34] then by Ghoman et al [35] and Poole et al [36]. Ghoman et al [35] used a series of supercritical aerofoils to derive the modes and showed that other supercritical aerofoils could efficiently be reconstructed.…”
Section: F Svd Methodsmentioning
confidence: 99%
“…Consequently the choice of shape parameterisation method can have a significant impact on the effectiveness and efficiency of the overall procedure [3]. Many different methods have been used within an aerodynamic optimisation framework, from standard geometric curve definitions such as B-Splines [4] or NURBS [5] to aerospace-specific methods such as CST [6,7], Hicks-Henne bump functions [8,9] or PARSEC [9,10] to Free-Form Deformation [11,12,13,14], proper orthogonal decomposition [2,15,16] or the discrete method [17]. A whole variety of options are available, however all are subject to the 'curse of dimensionality'.…”
Section: Introductionmentioning
confidence: 99%
“…Consequently the choice of shape parameterisation method can have a significant impact on the effectiveness and efficiency of the overall procedure 3 . Many different methods have been used within an aerodynamic optimisation framework, from standard geometric curve definitions such as B-splines 4 or NURBS 5 to aerospace-specific methods such as CST 6,7 , HicksHenne bump functions 8,9 or PARSEC 9,10 to Free-Form Deformation [11][12][13][14] , proper orthogonal decomposition 2,15,16 or the discrete method 17 . All of these approaches are subject to the 'curse of dimensionality'; in the context of aerodynamic optimisation this refers to the problems associated with increasing the number of design variables used in the optimisation procedure.…”
Section: Introductionmentioning
confidence: 99%